2015
DOI: 10.1097/j.pain.0000000000000319
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H4 receptor activation alleviates neuropathic pain through differential regulation of ERK, JNK, and P38 MAPK phosphorylation

Abstract: Histamine plays a complex role in pain modulation with opposite roles in nociception for histamine receptor subtypes 1, 2, and 3. The histamine H4 receptor (H4R) is expressed primarily on cells involved in inflammation and immune responses with a proinflammatory activity, but little is known about the role in nociception of neuronal H4R. To investigate the effects of neuronal H4R in pain transmission, the effects produced by the H4R agonist ST-1006 were detected in the spared nerve injury model of neuropathic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 47 publications
3
67
1
Order By: Relevance
“…In contrast, recently published papers revealed that H 4 R stimulation exhibited pain-reducing effects [3840]. Taken together, all these data suggest that H 4 R antagonists might possess anti-hyperalgesic properties that are secondary to decreased release of inflammatory mediators, whereas activation of neuronal H 4 Rs, especially those localized on sensory dorsal root ganglion neurons, might result in antinociceptive effects in the absence of inflammation [39]. …”
Section: Discussionmentioning
confidence: 95%
“…In contrast, recently published papers revealed that H 4 R stimulation exhibited pain-reducing effects [3840]. Taken together, all these data suggest that H 4 R antagonists might possess anti-hyperalgesic properties that are secondary to decreased release of inflammatory mediators, whereas activation of neuronal H 4 Rs, especially those localized on sensory dorsal root ganglion neurons, might result in antinociceptive effects in the absence of inflammation [39]. …”
Section: Discussionmentioning
confidence: 95%
“…Sanna et al [119] studied the effects of agonism of neuronal H4 receptors in pain transmission. They found that activation of H4 receptors, primarily in the dorsal root ganglia, resulted in altered MAP kinase signaling and ultimately decreased pain transmission [119].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
“…They found that activation of H4 receptors, primarily in the dorsal root ganglia, resulted in altered MAP kinase signaling and ultimately decreased pain transmission [119]. H4 receptor agonists are currently an active area of research, with some compounds being studied in clinical trials [120].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
“…Effects on H4 receptors block in NP models are also still not clear. A study has shown that treatment with H4 agonists blocks mechanical sensitivity, while others have shown that systemic use of H4 antagonists has dose-dependent and reversible effect on mechanical hypersensitivity 33 . Histamine effect on NP is clearly shown, however further studies are needed before considering the use of selective histamine agonists/antagonists to manage NP 6 .…”
Section: Histaminementioning
confidence: 99%
“…Peripheral and spinal activation of H3 receptors inhibits formalin-induced nociception 32 . Systemic administration of H3 receptors antagonists decreases mechanical sensitivity in experimental NP models 33 . In spite of the poor knowledge on the antinociception mechanism of anti-H3, they are already being clinically tested.…”
Section: Histaminementioning
confidence: 99%